Determining Induction Conditions for Expression of Truncated Diphtheria Toxin and Pseudomonas Exotoxin A in E. coli BL21 - Amoozadeh, Sahel; Hemmati, Maryam; Farajollahi, Mohammad Morad; Akbari, Neda; Tarighi, Parastoo (Novelty in Biomedicine, 2018)
Background: Targeted cancer therapies have played a great role in the treatment of malignant tumors, in the recent years. Among these therapies, targeted toxin therapies such as immunotoxins, has improved the patient’s survival rate by minimizing the adverse effect on normal tissues, whereas delivering a high dose of tumoricidal agent for eradicating the cancer tissue. Immunological proteins such as antibodies are conjugated to plant toxins or bacterial toxins such as Diphtheria toxin (DT) and Pseudomonas exotoxin A (PE) . In this case optimizing and expressing Diphtheria toxin and Pseudomonas exotoxin A which their binding domains are eliminated play a crucial role in producing the desired immunotoxins. Materials and Methods: We expressed the truncated DT and PE toxin in a genetically modified E.coli strain BL21 (DE3). For this reason we eliminated the binding domain sequences of these toxins and expressed these proteins in an expression vector pET28a with the kanamycin resistant gene for selection. The optimization of Diphtheria toxin and Pseudomonas exotoxin A expression was due to different IPTG concentration, induction and sonication time. Results: We observed that the optimal protein expression of the Diphtheria toxin was gained in 4 hours of 0.4 mM IPTG concentration at 25˚C on the other hand the optimization of Pseudomonas exotoxin A protein occurred in 4 hours of 0.5 mM IPTG concentration at 25 ˚C. Conclusion: Our study also showed lower IPTG concentrations could result in higher protein expression. By optimizing this procedure, we facilitate the protein production which could lead to acceleration of the drug development.